The origin of snakes : morphology and the fossil record - Caldwell, Michael Wayne (Boca Raton : CRC Press, 2020)
This book presents perspectives on the past and present state of the understanding of snake origins. It reviews and critiques data and ideas from paleontology and neontology (herpetology), as well as ideas from morphological and molecular phylogenetics. The author reviews the anatomy and morphology of extant snakes. Methods are also critiqued, including those empirical and theoretical methods employed to hypothesize ancestral ecologies for snakes. The modern debate on squamate phylogeny and snake ingroup phylogeny using molecules and morphology is examined critically to provide insights on origins and evolution. Key Features Important major evolutionary transformation in vertebrate evolution Continuing historical debate in vertebrate paleontology Of wide interest to a core audience of paleontologists, herpetologists, and morphologists Author acknowledged as prominent contributor to debate over snake origins Based on remarkable well preserved fossil specimens
Introduction. Modern Snakes. What is a Snake?. Ancient Snakes -- The Fossil Record. Burrowing Snakes, Fossil Snakes, and the Origins Debate. Discovering the "Ancestral Snake." Snake Palaeoecology: Reading the Rocks for Habits and Habitats. Snake Phylogeny. Origins: Where, When, Who and How. Conclusions: Where Next?
OCLC-licensed vendor bibliographic record.
Keywords: Snakes -- Origin; Snakes -- Evolution; NATURE / Animals; SCIENCE / Life Sciences / Evolution; SCIENCE / Earth Sciences / Geology